2017
DOI: 10.1596/1813-9450-8013
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Resilience of Peru's Road Network to Climate Events

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…They found that in provinces with high flood risk and low redundancy, the direct benefits of investments in new culverts and stronger bridges were relatively small given the low traffic volumes on these roads; however, the indirect benefits expressed in reduced expected annual road user costs due to flood disruptions were four times higher and largely justified the investments under most scenarios considered. Similar results were found in Peru, where Rozenberg et al (2017) showed that targeted investments to increase the redundancy of the road network around the Carretera Central, a strategic export route for agricultural products, could be justified on the sole basis of avoiding expected annual user losses due to flood and landslide disruptions ( Figure 15). Source: Rozenberg et al (2017) Redundancy can also be achieved through multi-modal transport planning.…”
Section: Criticality Analysis: Investing Where It Matterssupporting
confidence: 69%
See 2 more Smart Citations
“…They found that in provinces with high flood risk and low redundancy, the direct benefits of investments in new culverts and stronger bridges were relatively small given the low traffic volumes on these roads; however, the indirect benefits expressed in reduced expected annual road user costs due to flood disruptions were four times higher and largely justified the investments under most scenarios considered. Similar results were found in Peru, where Rozenberg et al (2017) showed that targeted investments to increase the redundancy of the road network around the Carretera Central, a strategic export route for agricultural products, could be justified on the sole basis of avoiding expected annual user losses due to flood and landslide disruptions ( Figure 15). Source: Rozenberg et al (2017) Redundancy can also be achieved through multi-modal transport planning.…”
Section: Criticality Analysis: Investing Where It Matterssupporting
confidence: 69%
“…Similar results were found in Peru, where Rozenberg et al (2017) showed that targeted investments to increase the redundancy of the road network around the Carretera Central, a strategic export route for agricultural products, could be justified on the sole basis of avoiding expected annual user losses due to flood and landslide disruptions ( Figure 15). Source: Rozenberg et al (2017) Redundancy can also be achieved through multi-modal transport planning. Urban planning, for example, can include non-motorized modes such as walking and cycling, and mass transit.…”
Section: Criticality Analysis: Investing Where It Matterssupporting
confidence: 69%
See 1 more Smart Citation
“…However, most of the available tools to assess the impact of disruption in transport systems rest on network theory and the concept of percolation 5,6 . Based on data on vehicles, passengers and freight, impacts are measured by the increase in travel time 7 , loss of accessibility 8 or quantities of blocked flows 9,10 . Such indicators can then inform infrastructure planning 11 .…”
mentioning
confidence: 99%
“…Note that economic resilience, as defined in this paper, is different from the resilience of the transport infrastructure itself to shocks. Literature on this topic exists (see, e.g., Rozenberg, Briceno‐Garmendia, Lu, Bonzanigo, & Moroz, ), but it is not a direct subject of interest for this review.…”
mentioning
confidence: 99%